Analisis Hubungan antara Inflasi, Pengangguran, dan Deflasi dalam Stabilitas Ekonomi Nasional - Intan Ratnasari; Dwi Aprilia; Maulidiyah Al Adawiyah; Della Wahyuningsih; Diva Nazmi Laila; Siti Ayu Juliyah; Ana Sahroni; Apriyanto Apriyanto (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
Inflation, unemployment, and deflation are three fundamental macroeconomic phenomena that are closely interconnected in influencing a nation’s economic stability. These variables illustrate the equilibrium between production capacity, consumption behavior, and government intervention in achieving sustainable economic growth. The main purpose of this study is to explore the interrelationship between inflation, unemployment, and deflation, and to assess their implications for Indonesia’s economic stability. This research applies a qualitative descriptive method, employing literature reviews, document analysis, and secondary data evaluation derived from credible institutions such as the Central Bureau of Statistics (BPS), Bank Indonesia (BI), and the Ministry of Finance. The results suggest that a moderate level of inflation can positively stimulate economic expansion through increased consumption and investment activities. In contrast, excessive inflation tends to erode consumer purchasing power and potentially elevate unemployment rates. Meanwhile, prolonged deflationary conditions may lead to a decline in product prices, reduced business profitability, and slower economic momentum. The interaction among these three factors is complex and dynamic, necessitating a coordinated balance between fiscal and monetary policies to safeguard overall economic stability. This study concludes that effective inflation control, job creation, and deflation prevention are critical elements in strengthening Indonesia’s long-term economic resilience.